1999
DOI: 10.2149/tmh1973.27.1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of antibodies to Parastrongylus cantonensis in human sera by gelatin particle indirect agglutination test.

Abstract: Abstract:A newly developed agglutination test using gelatin particles as an antigen carrier (GPAT) was compared with a conventional enzyme-linked immunosorbent assay (ELISA) for the detection of Parastrongylus cantonensis antibodies in sera from patients. A total of 70 sera was used in the study. Of these, 10 each were from patients with parastrongyliasis, gnathostomiasis, paragonimiasis, cysticercosis, toxocariasis, filariasis and malaria.The control group consisted of 50 serum samples from normal healthy ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Consequently, over the past decades a great number of immunological tests have been developed to enable the diagnosis of this human angiostrongyliasis [13], [14]. These approaches include an Indirect Enzyme Linked Immunosorbent Assay (ELISA) using a 31-kDa glycoprotein from the adult worm [8], [15], [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, over the past decades a great number of immunological tests have been developed to enable the diagnosis of this human angiostrongyliasis [13], [14]. These approaches include an Indirect Enzyme Linked Immunosorbent Assay (ELISA) using a 31-kDa glycoprotein from the adult worm [8], [15], [16].…”
Section: Introductionmentioning
confidence: 99%
“…The suspected diagnosis can only be confirmed upon finding and identification of A. cantonensis worms from the cerebrospinal fluid of infected patients, but this rarely occurs [10] – [12] . Consequently, over the past decades a great number of immunological tests have been developed to enable the diagnosis of this human angiostrongyliasis [13] , [14] . These approaches include an Indirect Enzyme Linked Immunosorbent Assay (ELISA) using a 31-kDa glycoprotein from the adult worm [8] , [15] , [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Indirect ELISA. ELISA was based on the methods described in Eamsobhana et al 19 with the following modifications: optimal concentration of antigen and serum (positive control) was determined by checkerboard titration. A concentration of 1:200 for primary antibody was derived by titration of positive and negative serum controls with a range of 1:100 to 1:1,000.…”
Section: Methodsmentioning
confidence: 99%
“…The 31-kDa proteins were first evaluated in 1997, 50 and subsequently shown to have sensitivity and specificity of 100% for detection of antibodies against A. cantonensis . 51 Serological analysis of CSF or serum was compared with real-time PCR and found that the immunodiagnosis was in agreement for 24 of the 26 patients. 49 However, this study 49 used crude antigen ELISA and Western blots (WB), not the isolated 31-kDa proteins.…”
Section: Introductionmentioning
confidence: 99%
“… 54 The gel-isolated and purified 31-kDa antigen has been used most consistently in studies conducted in Thailand. 55 59 In these Thailand trials, the glycoproteins comprising the purified 31-kDa antigen have shown 100% sensitivity and 98.72% specificity, and a rapid test kit has been patented. 59 , 60 …”
Section: Introductionmentioning
confidence: 99%